Educational needs of chronic kidney disease patients who presented to Tengku Ampuan Afzan Hospital: Preliminary findings - Sowtali, Siti Noorkhairina; Harith, Sakinah; Mohd Shah, Azarisman Shah; Ishak, Nur Ain'; Mohd Yusoff, Dariah; Draman, Che Rosle; Mohd Rasani, Ali Aminuddin; Ghazali, Norhasyimah (Saudi Journal of Kidney Diseases and Transplantation, 2020)
Knowledge limitation is a major cause of the increasing number of chronic kidney disease (CKD) patients in Malaysia and the world. Nurses are responsible for identifying the patients’ needs to come up with appropriate discharge plans which might include educational activities. The objective of this study was to determine the baseline information (sociodemographic background, as well as medical and lifestyle histories), along with educational needs of CKD patients. A total of 116 CKD patients who attended the Nephrology Clinic of Hospital Tengku Ampuan Afzan were recruited. Patients who fulfilled the inclusion criteria were selected between April and May 2017. Data were obtained via semi-guided questionnaires; the patients were given enough time to complete the required items. The CKD educational needs’ assessment consisted of seven domains: general information, chronic illness management, complications, self-management, medications, treatment, and financial status. Majority of the patients were men (53.4%), aged 54.65 ± 16.49 years, secondary school-finishers (49.1%), and jobless (48.3%). In terms of medical and life-style histories, most patients were diagnosed with end-stage renal disease (51.7%), hypertension (96.6%), diabetes (51.7%), and anemia (25.9%). The patients were interested to know the complications of kidney disease (57.8%), management of diseases like hypertension (58.6%), complications like edema (55.2%), indications for medication (73.3%), self-management or fluid control (37.9%), hemodialysis (37.1%), and financial status (21.6%). Thus, strengthening patient education strategies in the clinics, hospitals, and community settings should be given due attention by relevant healthcare professionals.